Sistem Pemesanan dan Pembayaran Menggunakan Teknologi Quick Response Code (QR Code) Berbasis Web pada Kedai Cangkir Gubug - Budi Hartono; Danang Danang (Jurnal Manajemen Informatika & Teknologi, 2021)
The results of this study are in the form of a product, namely an android application, an ordering and payment system using Android-based QR Code technology. According to the research design, the research results go through two testing or validation processes, namely design validation by experts in this case expert lecturers in the computer field, and product validation by users.Validation is carried out using an assessment instrument in the form of a questionnaire or validation sheet. The questionnaire contains 10 questions that must be filled in with a value between 1 and 4. The total score will get a score of not good, enough, good, or very good. The final conclusion is a statement that the product must be replaced, can be used with many revisions, can be used with few revisions, or can be used without revision.The results of the design validation test by experts gave a total score of 37, included in the score indicator 31 n 40, namely "Very Good". The conclusion drawn by the expert for system design is "Can be Used Without Revision".The results of product validation testing by users give an average value of 35 so that it is in the indicator category and gets the "Very Good" predicate. The final conclusion of user validation is a product or prototype "Can Be Used Without Revision".This research was conducted in a restaurant, Restaurant isn’t just a place to eat something but also a place to relaxing, meet someone or hang out with friends or colagues. Service of the restaurant is the main factor to make customer feel comfortable and relax. Many restaurant make their own order and payment system for better service but they forgot about the speed of their services.Using research methods data collection, observation, and interviewin Kedai Cangkir Gubug, face to face service like greeting, take order, and serving order all of it is waiter’s job. All of that tasks need time at most that makes if the restaurant have many customers, every single customer have to wait for a longer time waiting for waiter that serving another customer. The payment method is quite troublesome for customer because they have to save order paper for payment in cashier later.The solution that writer’s made is to decrease the task of waiter so that services can be done equally with QRcode technology for ordering menu with the scanner is android smartphone. Payment only need name of customer or table number and customer can do it in cashier or they can request the bill at their table. Therefore waiter no need to take order one after another and customer can do payment easier.